PENGEMBANGAN TRAINER PENGUAT DAYA AUDIO POWER AMPLIFIER OCL (OUTPUT CAPACITOR LESS) PADA MATA PELAJARAN PERENCANAAN DAN INSTALASI SISTEM AUDIO VIDEO DI SMK NEGERI 3 SINGARAJA - Gede Asmara Yudha; Nyoman Santiyadnya; I Gede Ratnaya (Universitas Pendidikan Ganesha, 2022)
This study aims to create an OCL Audio Power Amplifier Trainer media, to know the feasibility, and to know the students' responses. This research was conducted in the R & D (Research and Development) model. The research uses a questionnaire or questionnaire as an instrument of data collection by content experts, media experts, and students. From the research results obtained: media trainer can be made content expert validation test results obtained a percentage value of 98.3% with very decent qualifications, media expert validation test results obtained a percentage of 96.6% with very decent qualifications, small group test results score the lowest respondents were respondents R1, R3, and R5 with a score of 41, the score was classified as very good, the results of the large group test resulted in the lowest respondent's score being in respondent A8 with a score of 40, the score was classified as very good. Based on the results of the research, the OCL Audio Power Amplifier Trainer media is suitable for use in the learning process on the subject of Planning and Installation of Audio Video Systems in the Audio Video Expertise Program (TAV) of SMK Negeri 3 Singaraja.